The role of dietary education and vitamin supplementation in the treatment of Allergic Rhinitis - Kaczynska, Agnieszka; Gorecka, Adrianna; Osial, Natalia; Klosinska, Martyna; Chmiel, Paulina (Journal of Education, Health and Sport, 2022)
Introduction and purpose Allergic rhinitis (AR) is a widely prevalent condition which affects mainly children. The disease is not as severe as other allergic disorders; however, its symptoms significantly impact the patient's quality of life. The therapeutic options have limited effectiveness and they are burdened with numerous side effects. In addition, AR’s underlying causes are not fully elucidated; thus, there is an urgent need to conduct more large sample studies on this topic. State of knowledge In recent years, research concerning the role of vitamin deficiency in AR pathogenesis gathered pace. Some studies report that children with vitamin A, C and D deficiencies more often suffer from allergic diseases, especially AR and asthma. Furthermore, they are more likely to have severe infections and other disorders caused by immune imbalance. The crucial aspect of vitamins' role in AR is their significant ability to modulate the immune response, especially adaptive, by restoring Th1/Th2 balance. Recent publications reported that vitamin supplementation in AR patients results in an improved clinical course of the disease and restored immune balance. Moreover, vitamins added to the typical treatment improve its effects. Conclusions This review aims to summarize the state of knowledge about the role of vitamin A, C and D deficiency in the pathogenesis of AR. Moreover, we point out the values of education in the field of proper dietary habits among AR patients. In addition, the effects of vitamin supplementation in AR patients are also emphasized.